Functional imaging as a predictor of schizophrenia. - Whalley, H; Simonotto, E; Moorhead, W; McIntosh, A; Marshall, I; Ebmeier, K; Owens, D; Goddard, N; Johnstone, E; Lawrie, S (2006)
BACKGROUND: Prospective studies of young individuals at high risk of schizophrenia allow the investigation of whether neural abnormalities predate development of illness and, if present, have the potential to identify those who may become ill. METHODS: We studied young individuals with at least two relatives with the disorder. At baseline functional magnetic resonance imaging (fMRI) scan, none met criteria for any psychiatric disorder, but four subjects subsequently developed schizophrenia. We report the baseline functional imaging findings in these subjects performing a sentence completion task compared with normal control subjects (n = 21) and those at high risk with (n = 21) and without (n = 41) psychotic symptoms who have not developed the disorder. RESULTS: High-risk subjects who became ill demonstrated increased activation of the parietal lobe, decreased activation of the anterior cingulate, and smaller increases in activation with increasing task difficulty in the right lingual gyrus and bilateral temporal regions. The hypothesized predictive power of parietal activation was supported only in combination with lingual gyrus activity, which gave a positive predictive value in this sample of .80. CONCLUSIONS: Although these findings should be considered cautiously, as only four subjects who had an fMRI scan subsequently became ill, they suggest functional abnormalities are present in high-risk subjects who later became ill, which distinguish them not only from normal control subjects but also those at high risk who had not developed the disorder. These differences are detectable with fMRI and may have clinical utility.